The perils of proximity : China-Japan security relations - Bush, Richard C., 1947-; Brookings Institution (Washington, D.C. : Brookings Institution Press, 2010)
'Explores the factors underlying the security dilemma confronting Japan and China despite their positive economic interaction, including China's growing military capability, the Japan-U.S. security alliance, and issues such as Japan's occupation of China in the mid-twentieth century and rights in the East China Sea'--Provided by publisher.
Includes bibliographical references and index.
Keywords: National security -- Japan; National security -- China; Japan -- Military relations -- China; China -- Military relations -- Japan